Revitalizing Islamic Education Through the Paradigm of Tawhid Ismail Raji Al- Faruqi - Mardatillah, Nur aprilda; DEWI, EVA; Rahayu, Tia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the revitalization of Islamic education through the concept of the Tawhid paradigm proposed by Ismail Raji al-Faruqi. Using a library research method, the study explores five principles of unity: God, creation, truth and knowledge, life, and humanity, as an integrative framework between revelation and reason. The findings indicate that the Tawhid paradigm serves as both an epistemological and axiological foundation for reconstructing Islamic education to overcome the dichotomy between religious and scientific knowledge. Through the Islamization of knowledge project, al-Faruqi proposes twelve strategic steps for educational reform, including mastery of modern sciences, reexamination of classical heritage, development of an integrative curriculum, and research methodologies based on divine revelation. This approach fosters learners who are balanced intellectually, spiritually, and morally. The revitalization of Islamic education based on the Tawhid paradigm aims to restore the unity of knowledge and faith, shaping a generation of ulul albab capable of integrating scientific rationality with ethical and spiritual awareness in facing the challenges of modernity.